Memorandum of Understanding between the International Livestock Research Institute (ILRI) and National Meteorology Agency - International Livestock Research Institute; National Meteorological Agency (2022)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and National Meteorology Agency. MOU signed on December 23, 2021, by Jimmy Smith, Director-General of ILRI and Fetene Teshome, Director-General of National Meteorology Agency.